Clinical actionability and utilization of next-generation sequencing for prostate cancer in a changing treatment landscape - Griffin, Jacqueline; Tsao, Che-Kai; Patel, Vaibhav; Liaw, Bobby C.; Guin, Sunny; Joshi, Himanshu; Rossi, Michael; Hantash, Feras; Zhou, Xiang; Tewari, Ash; Galsky, Matthew D.; Oh, William K.; et al. (Frontiers in Urology, 2022)
Background Until recently there were no genome-directed therapies (GDTs) requiring next-generation sequencing (NGS) in prostate cancer. We examined whether the US approval of poly-(ADP-ribose) polymerase (PARP) inhibitors in May 2020 influenced the actionability and utilization of NGS in patients with prostate cancer. Methods This was a single-center, retrospective study including men with prostate cancer who received NGS testing from a single lab between 7/11/2018-7/6/2021. Clinical and testing data were derived from the electronic medical record. Results There were 346 patients with prostate cancer and qualifying NGS testing during the study period. Overall, 55 patients (15.9%) had qualifying homologous recombination repair (HRR) alterations for PARP inhibitor treatment. A greater proportion of alterations were actionable post-approval compared to pre-approval (22.7% vs 0%, Chi-squared p<0.001). 9 patients received olaparib during the study period. Patients receiving NGS testing after the PARP inhibitor approval were more likely to have metastatic disease than patients sequenced before the approval (74.2% vs. 41.1% Chi-squared p<0.001). Only 10.4% of patients with metastatic prostate cancer received NGS testing within 30 days of diagnosis. NGS testing was performed after a median of 1 prior line of systemic therapy. The median number of days between metastatic diagnosis and NGS testing was 196 (Q1-Q3: 54-832). The median time from NGS testing to the next treatment was 255 days (95% CI 151-300). These characteristics were not significantly different before or after the PARP inhibitor approval. Conclusion In this single-center cohort, the approval of PARP inhibitors for later-line treatment of metastatic prostate cancer increased the actionability of NGS findings but did not lead to earlier use of NGS testing.